Kabbalah and the Spiritual Quest: The Kabbalah Centre in America - Gubkin, Liora (Sociology of religion, 2010)
Esoteric mystical traditions are often the well-kept secrets of a small elite, and Kabbalah—the ancient Jewish mystical tradition—is no exception. The transmutation of Jewish mystical teachings to a universal source of wisdom and healing through the auspices of the Kabbalah Centre provides a fascinating episode for scholars of both Judaism and sociology of religion. In Kabbalah and the Spiritual Quest, Jody Myers offers a portrait of the Kabbalah Centre in America: delineating its history and explaining its main teachings, especially its understanding of individual and communal healing., A historian by training, Myers provides a service to sociologists of religion by analyzing the Kabbalah Centre as a New Religious Movement.